Juan Vicente Gómez (Wikipedia, 2017)
Juan Vicente Gómez Chacón (24 July 1857 – 17 December 1935) was a military general and de facto ruler of Venezuela from 1908 until his death in 1935. He was president on three occasions during this time, and ruled as an unelected military strongman for the rest of the era.
Page Version ID: 793306353